SPE Annual Technical Conference and Exhibition 1988
DOI: 10.2118/18092-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pilot Polymer Flood in the Marmul Field, Oman

Abstract: In view of the high permeability, fairly high oil viscosity, moderate reservoir temperature, low salinity formation water and availability of low salinity injection water, the Marmul Al Khlata formation was considered a good candidate for polymer flooding. A pilot consisting of an polymer flooding. A pilot consisting of an unconfined 5-spot on a 200 m spacing was initiated in May 1986. After the injection of a water preflush of 0.23 PV, a polymer slug of 0.63 PV and preflush of 0.23 PV, a polymer slug of 0.63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 2 publications
1
28
0
1
Order By: Relevance
“…India also reports a polymer flood in Sanand Field [99,100]. Oman also documented a polymer flood pilot developed in Marmul Field [101] and almost twenty years later a large-scale application is under way [18]. Additionally, Argentina (El Tordillo Field), Brazil (Voador offshore Field), Canada (Horsefly Lake Field) and Germany (Bochstedt Field) announced plans to implement polymer flood projects [18].…”
Section: Chemical Methodsmentioning
confidence: 99%
“…India also reports a polymer flood in Sanand Field [99,100]. Oman also documented a polymer flood pilot developed in Marmul Field [101] and almost twenty years later a large-scale application is under way [18]. Additionally, Argentina (El Tordillo Field), Brazil (Voador offshore Field), Canada (Horsefly Lake Field) and Germany (Bochstedt Field) announced plans to implement polymer flood projects [18].…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Finally, Haynes, A. K., Clough, M. D., Fletcher, A. J. P., & Weston, S., (2013) reported that the rate at which fracture growth occurred was unknown. Choudhuri et al, 2013;Choudhuri et al, 2014;Koning and Mentzer, 1988;Shuaili et al, 2012;Thakuria et al, 2013;Zwaan and Valdez, 2015). This field was discovered in 1956 and started commercial production in 1980.…”
Section: Polymer Injection Ratesmentioning
confidence: 99%
“…Numerous successful worldwide field-scale chemical flooding (Polymer, SP and ASP) projects have been documented in the literature. Koning et al (1988) reported a total oil production of 59% STOIIP from Al Khlata formation of Marmul field. Takagi et al (1992) OOIP by polymer flooding at Daqing field, primarily due to the increase in displacement efficiency and volumetric sweep efficiency.…”
Section: Past Field Projects Of Chemical Floodingmentioning
confidence: 99%